2018
DOI: 10.1016/j.brs.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

A distinct biomarker of continuous transcutaneous vagus nerve stimulation treatment in major depressive disorder

Abstract: The FC between the bilateral MH and rACC may serve as a potential biomarker for the tVNS state and predict treatment responses. Our results provide insights into the neural modulation mechanisms of continuous tVNS and reveal a potential therapeutic target for MDD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 63 publications
4
55
0
Order By: Relevance
“…This result is consistent with a previous study using the same data set, in which we found that DLPFC rsFC with the rACC significantly increased after Tai Chi [5] . Similar results have been observed after various exercise interventions (Tai Chi, Baduanjin, and stationary cycling) in patients with knee osteoarthritis and after transcutaneous vagus nerve stimulation in patients with depression [33] .…”
Section: Discussionsupporting
confidence: 83%
“…This result is consistent with a previous study using the same data set, in which we found that DLPFC rsFC with the rACC significantly increased after Tai Chi [5] . Similar results have been observed after various exercise interventions (Tai Chi, Baduanjin, and stationary cycling) in patients with knee osteoarthritis and after transcutaneous vagus nerve stimulation in patients with depression [33] .…”
Section: Discussionsupporting
confidence: 83%
“…Finally, tVNS could be used to further understand the processes mediating the clinical improvements brought about by VNS in epilepsy and depression, for example the role of arousal-promoting neuromodulatory signaling in improving mood in depressed patients (Grimonprez et al, 2015;Liu et al, 2016;Fang et al, 2017;Tu et al, 2018). In particular, tVNS-induced pupillary and EEG effects in individual patients could possibly predict the future clinical efficacy of invasive VNS and help guide triaging patients into either conservative therapy or surgical implantation of VNS stimulation devices.…”
Section: Vnsmentioning
confidence: 99%
“…Indeed, transcutaneous auricular vagus nerve stimulation (taVNS) was developed as a non-invasive variant of VNS where the vagus nerve is stimulated through the skin of the auricle (Fallgatter et al, 2003). Preliminary studies have shown that noninvasive taVNS improves mood (Kraus et al, 2007) and depressive symptoms (Liu et al, 2016;Tu et al, 2018;Wu et al, 2018) similar to invasive VNS. Such improvements could be due to alterations in brain activity in the prefrontal cortex and the limbic system after invasive (Nahas et al, 2007;Pardo et al, 2008) and noninvasive VNS (Badran et al, 2018;Yakunina et al, 2017).…”
Section: Introductionmentioning
confidence: 99%